Indonesian teachers’ senses of humor in teaching EFL classes: Students’ perceptions - Vico Taufiqul Huda; Hartono Hartono; Fardini Sabilah (English Learning Innovation, 2025)
The absence of good classroom climate sometimes makes students feel bored or even terrified with English lesson. Not only the students, but also teachers feel bored in teaching English in EFL classroom caused by the less ability in conducting interactive and positive classroom atmosphere. The goal of the current study is to examine the kinds of humor utilized by EFL teachers in East Java and the students’ perceptions toward them. This current study is a qualitative study and utilizes phenomenological research with descriptive questionnaires analysis. It is done in two Islamic Junior High schools in Jombang with two English teachers.  The data are collected through classroom observation, interview, and Questionnaire. The findings showed that the teachers utilized verbal/word-based humor, slapstick/physical humor, related humor, self-disparaging humor, unrelated humor, unplanned humor, riddle, and spontaneous humor. Meanwhile the total mean from the questionnaire analysis result is 41.377 that indicates students’ perceptions toward teachers’ utilization of humor as positive. By knowing the kinds of humor utilized as strategy of teaching EFL classes and students’ perceptions toward them, it is expected that EFL teachers can create positive classroom climate by delivering humor that can be appropriate for students and supporting them in learning.